Implementasi Fatwa DSN MUI Tentang Syariah Card Pada Produk BSI Hasanah Card - Halimatuzzahro, Rahma; Hadiati, Teti; Naimah, Khoridah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) Number 54/DSN-MUI/X/2006 concerning sharia cards explains the legal provisions regarding sharia financial products, especially Hasanah card products issued by Bank Syariah Indonesia (BSI). This research aims to analyze the application of this fatwa in the context of the BSI Hasanah Card which has been designed to meet people's needs in financial transactions without violating sharia principles. By analyzing the mechanism for using the contract, restrictions (dhawabith hudud) on card use such as (1) prohibition of usury, (2) prohibition of carrying out transactions that are not in accordance with sharia, (3) prohibition of excessive use (ishraf) by setting a maximum spending ceiling, (4) card holders must have the financial capacity to be able to pay when billing time arrives, (5) prohibition on providing facilities that are contrary to sharia, compensation costs (ta'widh) and late fines, as well as obstacles faced in implementing BSI Hasanah Card. This type of research is juridical-empirical using primary and secondary data collection techniques through observation, interviews and document study. The results of this research show that the BSI Hasanah Card product has aligned its use to be free from usury and the implementation of contracts in accordance with existing fatwas. However, there are discrepancies with the fatwa in certain matters, such as the application of compensation fees (ta'widh) and the lack of clear mapping regarding the blocking of product purchases which are only limited to the merchant, not the item or product.